Penerapan Analisis Cost Volume Profit sebagai Evaluasi dalam Merencanakan Laba melalui Integrasi Pendapatan pada UMKM Ayam Penyet Zianka - Erika, Erika; Nurwani, Nurwani; Jannah, Nurul (Penerbit Goodwood, 2024)
Purpose: This study aims to evaluate profit planning through revenue integration in the Ayam Penyet Zianka MSME by employing Cost Volume Profit (CVP) analysis. The objective is to understand how CVP analysis can help optimize financial performance and strategic planning in the competitive food service industry. Research methodology: A descriptive quantitative method was used, relying on a secondary data analysis. This study employed CVP analysis to assess the break-even point and margin of safety. By integrating various cost components and revenue streams, this analysis aims to identify the critical factors affecting profitability and provide actionable insights for financial management. Results: The analysis revealed several factors that contributed to the decline in sales and subsequent decreases in MSME profits. High operational costs hinder the effective cost control and production management processes. Additionally, fluctuating material prices that are not matched by corresponding increases in selling prices further exacerbate profit margins. These findings underscore the importance of efficient cost management and dynamic pricing strategies for sustaining profitability. Limitations: The study was confined to a single MSME, which may limit the generalizability of the findings. Moreover, reliance on secondary data may restrict the depth of the analysis and the ability to capture real-time financial nuances. Contribution: This study enhances profit planning strategies for small food businesses and contributes to improved financial management practices in the MSME sector. It provides valuable insights for entrepreneurial decision making, emphasizing the significance of CVP analysis in effective profit planning and financial performance optimization within competitive market dynamics. This study highlights the critical need to integrate cost-control measures and adaptive pricing strategies to sustain profitability in the face of market fluctuations.